Test Device for Liquid Moisture Transport Difference Evaluation of Fabrics - Bao-guo Yao; Shui-yuan Hong; Jian-chao Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A test device was developed and a test method was proposed to characterize the dynamic liquid moisture transport properties of textile fabrics, based on the mechanical equipment, microelectronics, sensors and control system. Derived from the test data, five indices were defined to characterize the dynamic liquid moisture transport difference between two surfaces of textile fabrics. The test principle, the structure of the mechanical equipment and the evaluation method for the dynamic moisture transport difference were introduced. Six types of fabrics made from different textile materials were measured. The one-way ANOVA analysis was carried out to identify the significance of the differences of the indices among the test fabrics. The results show that each evaluation index is significantly different (P